(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper deals with establishment, implementation and development of electronic prescription or e-Prescription in context with e-Health solutions. It includes introduction of a numerous innovative solutions, which are to be committed for data information flow, data management and functionality as well as of establishment of a new feasible communication forms between doctors, patients and pharmacists. The aim of the study is to describe some technical aspects and functionality of implementation of e-Prescription system for medical institutions, patients and pharmacies; and, calculation of the total cost of implementation (TCI) for Latvian individual pharmacies. Several expecting financial aspects, which have encompassed evaluation of TCI, calculating payback time, ROI, NPV, and IRR are to be calculated. On the bases of these financial calculations, the primary investment of implementation of e-Prescription for individual pharmacies and initial costs are determined. Impact on individual parts of TCI with the scope to individual pharmacy size, location, existence or absence of formal information strategy has calculated. According to collected data, research paper shows how proposed electronic system is going to implement among Latvian individual pharmacies.